Morphological variation of the maxilla in modern humans and African apes. Issue 168 (July 2022) - Hanegraef, Hester; David, Romain; Spoor, Fred
Abstract: Differences in morphology among modern humans and African apes are frequently used when assessing whether hominin fossils should be attributed to a single species or represent evidence for taxic diversity. A good understanding of the degree and structure of the intergeneric, interspecific, and intraspecific variation, including aspects such as sexual dimorphism and age, are key in this context. Here we explore the variation and differences shown by the maxilla of extant hominines, as maxillary morphology is central in the diagnosis of several hominin taxa. Our sample includes adults of all currently recognized hominine species and subspecies, with a balanced species sex ratio. In addition, we compared the adults with a small sample of late juveniles. The morphology of the maxillae was captured using three-dimensional landmarks, and the size and shape were analyzed using geometric morphometric methods. Key observations are that 1) the maxillae of all extant hominine species and subspecies show statistically significant differences, but complete separation in shape is only seen at the genus level; 2) the degree of variation is not consistent between genera, with subspecies of Gorilla being more different from each other than are species of Pan ; 3) the pattern of sexual shape dimorphism is different in Pan, Gorilla, and Homo, often showing opposite trends; and 4) differentiation between maxillary shapes is increased after adjustment for static intraspecific allometry. These results provide a taxonomically up-to-date comparative morphological framework to help interpret the hominin fossil record, and we discuss the practical implications in that context.